The writing of the history: Jean Pierre Fave an approach to the theory of story - Gómez Palomino, Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In the last forty years the historiography production in Colombia presents an important variety of methodological approaches that has allowed, at the same time, variety in the academic and editorial production, such as: collections, manuals, books, essays, doctoral theses, articles and research on specifics events. All this literature offers the academic community an important support for current studies and research, but is also an antecedent collection for the reflection on the writing of history from approach to the theory of the story of the French philosopher and historian Jean Pierre Faye. The article focuses on the postulation of the methodological principles of the Theory of the History, particularly in its relation to the theoretical-methodological influences of kantian rationality, Marxist political economy, the sacred sociology or power Bataille, French epistemology and chomskian linguistics. With this approach to the methodology of the Theory of the History, the article supports a novel historiography bet for the national academic environment, when describing and explaining, a powerful methodology for the studies of social and political history.